SOME CONSIDERATIONS ON THE FORMATION OF MEANS OF EXPRESSION OF THE CONCEPT OF CONSANGUINITY - Ulikova Mavludahan (Scholars Digest Publishing, 2023)
In World linguistics, the concept of cognitology is considered as a system of human activity, first of all, the perception, processing, storage of information and the use of this information in accordance with the situation. The concept is any discrete substantive unit of collective consciousness that reflects in the form of a substrate known in the national memory of language owners. Naturally, as in all other cognitive sciences, in cognitive linguistics, its main category is served by the “concept”, although it is a multifaceted mental - cognitive phenomenon. Including, our study is one such study, consisting in the study of the linguocultural and linguopragmatic peculiarities of means of expression of the blood-kin concept.
Keywords: the concept of cognitology, cognitive-semiological theory, perceptions of the universe, discrete content unit.